Marketing Manuvers Based on Jamaah Involved for Savings Products in Increasing of Customers at Microfinance - Amin, Moh. Roqibul; Mas’udi, Ahmad; Mannan, Abd.; Rahman, Fadali (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
Global competition is a fact in economic life that occurs not only in the goods market but also in the services market. Microfinance must have a marketing strategy to achieve optimal profits. Marketing strategy is a complex company activity in which there are interconnected marketing variables. This research aims to explore and describe how microfinance increases the number of customers based on jamaah-involved marketing maneuvers. This was conducted at KSPPS. BMT NU Bondowoso City Branch aims to find out the marketing manuveres used and the efforts made by KSPPS. BMT NU Bondowoso City Branch in increasing public interest in these savings products. This research was carried out using a data collection process utilizing observation, interviews, and documentation. Data processing is carried out through Editing, Organizing, and Analyzing, analysis is carried out with a case study. Marketing manuveres used by KSPPS. BMT NU Bondowoso City Branch is a marketing mix strategy that can increase public interest. This research shows that marketing manuveres were implemented in all 4P’s and extended the marketing mix widely.